Ledelse gennem narrativer - Hansen, Heidi (Academic Quarter | Akademisk kvarter, 2013)
Heidi Hansen describes how people create meaning through stories. An event or episode does not carry any meaning in itself but is assigned meaning through its constructed relations to other events and the way it is put into words. Stories create memory as well as oblivion and thus influence the identity of the organization as well as the identity of its members. Therefore it is a central management discipline to try to influence the dominant stories told in the organization.